RENOVASI AKUSTIK GEDUNG KONSER PASCASARJANA INSTITUT SENI INDONESIA (PS-ISI) YOGYAKARTA - Satwiko, Prasasto (Jurnal Arsitektur Komposisi, 2012)
Abstract: This paper reports an acoustical research project conducted as a scientific base for the renovation of the Concert Hall of Postgraduate Program, Indonesia Art Institute, Yogyakarta. The concert hall is intended mostly for classical music performances. The renovation has been limited by the form of the existing building, tight time schedule, budget, material provision as well as low labors’ skill. The research applied digital simulation method using Ecotect 5.5 and CATT v8. Testing conducted after construction process found that the simulation results could be reproduced well in the real world. The sound of the played music instrument fulfills the hall with clear details.Keywords: Classical music, acoustics, concert hall, computer simulationAbstrak: Makalah ini menyajikan hasil penelitian akustik sebagai landasan ilmiah renovasi gedung konser musik klasik Pascasarjana Institut Seni Indonesia Yogyakarta. Renovasi dibatasi oleh bentuk gedung yang sudah ada, waktu, biaya, bahan yang tersedia serta kemampuan dan keterampilan yang dimiliki oleh pekerja lokal. Metoda utama yang dipakai adalah simulasi digital dengan memakai software Ecotect 5.5 dan CATT v8. Uji coba yang dilakukan setelah proses konstruksi selesai menunjukkan bahwa hasil simulasi dapat diaplikasikan pada keadaan nyata dengan baik. Bunyi musik terasa hidup dan detail terdengar dengan baik.Kata kunci: Musik klasik, akustik, gedung konser, simulasi komputer